As políticas públicas e o direito humano à alimentação adequada no município de Foz do Iguaçu/PR (2010-2020) - Morais, Gabrieli Ribas de (2022)
This dissertation presents reflections about the Human Right to Adequate Food (HRAF) and the implementation of public policies on food and nutrition in the municipality of Foz do Iguaçu/PR. It intends to problematize the relationship between small family farmers and the implementation of these policies through municipal management. To this end, a theoretical debate on public policies for food and nutrition, food systems, and collective organizations is carried out in conjunction with a statistical analysis of interviews with family farmers in the region covered by COAFASO, municipal managers, and nutritionists from the municipal school lunch sector. We first seek to understand public policies for food purchasing, then analyze the implementation of these policies in the municipality of Foz do Iguaçu, and finally, we discuss the relationship between these policies and family farming